Studi Kasus: Pengaruh Kombinasi Terapi Butterfly Hug dan Expressive Writing terhadap Kecemasan Sosial pada Remaja Di Desa Kedunggede - Huria Husna Nabilah; Reza Fajar Amalia; Asep Iskandar (Journal of Bionursing, 2025)
Background. Adolescence is a transitional phase from childhood to adulthood with physical, psychological, and social changes, placing adolescents in a vulnerable phase in terms of establishing emotional balance. In addition, adolescents are very vulnerable to social insecurity due to a strong need for social acceptance, which causes social anxiety. The purpose of this study was to determine the effect of butterfly hug therapy and expressive writing on social anxiety in adolescents Methods. A case study with implementation based on evidence-based practice in nursing care Results. There was a change in the social anxiety scale from a score of 54 to 36 after administering butterfly hug therapy and expressive writing to adolescents. The social anxiety scale of adolescents after therapy showed an increase with a change of 1-2 scores on each item, namely the time needed to adjust, feelings of embarrassment when joining friends, confidence in their ability to complete a task, and verbal ability or openness of adolescents when answering questions Conclusion. The combination if butterfly hug therapy for 10 minutes over 6 sessions and expressive writing for 20 minutes over 5 sessions in six consecutive days had a positive effect on social anxiety levels. Clients felt calmer, their discomfort when interacting in social environments decreased, and they were able to make more rational assessments of the situations they faced.